The Influence of Conformity on Group Decisions in the Boalemo Police Environment - Fendi Ntobuo; Lenny Syamsuddin; Ramly Amat HI. Djafar (Journal of Community Health Provision, 2026)
This study aimed to examine the influence of conformity on group decision making in the Boalemo Police Department. The research employed a quantitative approach using simple linear regression analysis. The participants consisted of 30 members of the Boalemo Police Department selected through total sampling. Data were collected using conformity and group decision-making scales in the form of questionnaires. The results showed a significant positive relationship between conformity and group decision making, with a correlation coefficient of 0.604 and a significance value of p < 0.01. These findings indicate that higher levels of conformity are associated with higher levels of group decision making among members of the Boalemo Police Department. In the organizational context of the police, conformity appears to support consensus building, coordination, and the efficiency of collective decision-making processes. Thus, this study highlights that conformity is an important socio-psychological factor in shaping group decision making within a hierarchical work environment.